Waterworks and Water Systems in Sant’Agata dei Goti. Towards an Integrated Informative System (diségno, 2019)
The research presents an integrated description of an area in the Campania region between the slopes of the Taburno mountain range and the Terra di Lavoro hills with its numerous infrastructures and factories built from the seventeenth century onwards, small tiles in a cultural-landscape mosaic that still preserves the original engineering works for the supply and distribution of water resources.Before initiating the study a methodology had to be established to integrate the quantitative data –the geometric and dimensional characteristics of the buildings– with the qualitative data regarding the perception of the landscape and urban image as well as their possible visual appeal.The study focused on the network of manufacturing and pre-industrial activities along the river north of Sant’Agata dei Goti. The data gathered from historical, iconographic and archival documentation was combined with all the other information (position, orientation, characterisation of the water supply system) and with the data from the digital, photogrammetric and aerial photogrammetric survey.nThe goal was to create a structured and georeferenced database, organised according to formal, functional, and building types, so as to develop a useful tool to understand and enhance architectural and landscape heritage as well as promote initiatives involving con- servation and digital fruition.
Keywords: survey; information system; landscape; enhancement